838. ACONITUM JAPONICUM subsp. JAPONICUM: Ranunculaceae. (September 2016) - Kadota, Yuichi
Summary: The name Aconitum japonicum Thunb. subsp. japonicum (syn. A. japonicum var. montanum Nakai; Japanese name, Yama‐torikabuto) is well known to botanists and horticulturists as a representative of Japanese monkshoods and is occasionally found even in the suburbs of Tokyo. However, this aconite is restricted to the mountains on the Pacific Ocean side of Honshu Island, central Japan. Although the geographical range of A. japonicum is rather narrow, it shows a wide range of morphological variation as a member of a tetraploid species group (2n = 4x = 32).